Clinical cases in paediatrics : a trainee handbook - Anthony Cohn [ (Anthony Simon)] , 1966-; Reece, Ashley (JP Medical Publishers, 2014)
"Clinical Cases in Paediatrics : A Trainee Handbook provides a wealth of commonly encountered clinical scenarios, to enable trainees to manage paediatric cases more effectively. Featuring in-depth analyses, trainees are prompted to apply their knowledge to real-life clinical situations, and then reach a confident diagnosis and management plan. Covering the knowledge-base in a succinct and accessible format, this book provides the essential practical guide for paediatric trainees in the outpatient setting." --PUBLISHER.